WhysoSeriousGame: A conceptual framework for learning motivation through serious game - Marzita Mansor; Rohaizah Abdul Wahid; Suliana Sulaiman; Asma Hanee Ariffin; Nurathirah Azme (Pejabat Karang Mengarang UPSI, 2021)
The aim of this paper is to construct a framework for serious games' motivation in learning. Additionally, it attempts to emphasizes the importance of motivational factors as an integral component of serious games for university students. Existing research on serious games for university students' learning is insufficient, and students are reported to be discouraged from exploring serious games in their learning. Thus, the objective of this paper is to develop the WhysoSeriousGame framework in order to provide a comprehensive, serious game-based framework that emphasizes motivation as a critical aspect of learning. Additionally, this paper provides a description on how the framework can be implemented in teaching and learning for university students. The framework also serves as a source of reference for future Serious Game development.